2002
DOI: 10.1107/s1600536802023085
|View full text |Cite
|
Sign up to set email alerts
|

The chain structure ofcatena-poly[[(2-tert-butyltetrazole-κN4)copper(II)]-di-μ-chloro]

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean '(C±C) = 0.005 A Ê R factor = 0.035 wR factor = 0.098 Data-to-parameter ratio = 26.4For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Earlier studies reported that several tetrazole derivatives possess diverse pharmacological properties (Juby et al, 1968(Juby et al, , 1982. However, crystallographic studies of only a few complexes of monosubstituted tetrazole derivatives have been reported (van den Heuvel et al, 1983;Lyakhov et al, 2003). Here, we report the synthesis and structure of the title novel tetrazole thioether, (I).…”
Section: Commentmentioning
confidence: 84%
“…Earlier studies reported that several tetrazole derivatives possess diverse pharmacological properties (Juby et al, 1968(Juby et al, , 1982. However, crystallographic studies of only a few complexes of monosubstituted tetrazole derivatives have been reported (van den Heuvel et al, 1983;Lyakhov et al, 2003). Here, we report the synthesis and structure of the title novel tetrazole thioether, (I).…”
Section: Commentmentioning
confidence: 84%
“…217,218 As the substituent bulk increases (R = Pr, CH 2 =CHCH 2 ), both tetrazole ligands become bridging and are coordinated by the N(4) and N(1) atoms (structure 130). 219 Note that complexes 128 ± 130 are the first examples of layered polymeric structures formed by N-substituted tetrazoles through two nitrogen atoms of the heterocycle. The complexes CuLCl 2 and Cu 3 L 4 Cl 6 are polymeric chains 131 and 132, respectively, formed owing to the bridging coordination of chlorine atoms; 220 ± 222 in 132, the neighbouring copper atoms are additionally linked by the tetrazole ring [N(3), N(4) atoms]; hence, a half of the tetrazole ligands in the structure are bridging.…”
Section: Metal Derivatives Of Neutral N-substituted Tetrazolesmentioning
confidence: 99%
“…A series of¯exible or rigid chain-linked dithioethers containing N-heterocyclic moieties have been synthesized and investigated (Sharma et al, 1999;Constable et al, 2002;Bu et al, 2003;Hong et al, 2000;. Earlier studies have shown that several tetrazole derivatives possess diverse pharmacological properties (Juby et al, 1968(Juby et al, , 1982, but only a few metal complexes of monosubstituted tetrazole derivatives are known (van den Heuvel et al, 1983;Lyakhov et al, 2003). We report here the synthesis and structure of a new tetrazole dithioether, namely 1,2-bis(1phenyl-1H-tetrazol-5-ylsulfanyl)ethane, (I).…”
Section: Commentmentioning
confidence: 99%